1993
DOI: 10.1001/archinte.1993.00410210044006
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibition and Renal Protection

Abstract: The role of hypertension in the pathogenesis of renal damage is a subject of both historical interest and current investigation. Because of the difficulty associated with studying the pathophysiologic role of glomerular injury in systemic hypertension, experimental models have provided much of the data in this field. The mechanisms leading to glomerular injury are complex and not fully elucidated. Mesangial and endothelial cell injury are thought to be important pathophysiologic mechanisms in the renal injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Several other trials showed that ACE inhibitors clearly reduce albuminuria in both type I and type II diabetes mellitus, irrespective of blood pressure level, with consistent antiproteinuric effects. 12,[18][19][20][21][22][23][24][25][26][27][28][29] Although evidence from these studies has been interpreted as clearly demonstrating the beneficial renal effects of ACE inhibitors, there have been dissenting opinions [30][31][32][33][34][35][36][37] and calls for definitive long-term clinical trials to provide proof for the postulated effects. 38 One of the central issues in interpreting these and other studies on this issue revolves around the choice of outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Several other trials showed that ACE inhibitors clearly reduce albuminuria in both type I and type II diabetes mellitus, irrespective of blood pressure level, with consistent antiproteinuric effects. 12,[18][19][20][21][22][23][24][25][26][27][28][29] Although evidence from these studies has been interpreted as clearly demonstrating the beneficial renal effects of ACE inhibitors, there have been dissenting opinions [30][31][32][33][34][35][36][37] and calls for definitive long-term clinical trials to provide proof for the postulated effects. 38 One of the central issues in interpreting these and other studies on this issue revolves around the choice of outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperkalemia could be extremely harmful in patients who have renal insufficiency, are diabetic, and in those using nonsteroidal anti-inflammatory drugs and salt substitutes (Ben Salem et al 2014). Renal impairment is another possible side effect of ACE-Is, induced by reduced renal perfusion due to inhibition of angiotensin II (Hollenberg 1985). Other common side effects include headache, dizziness, rash, and fever.…”
Section: Adverse Effects Of Ace-ismentioning
confidence: 99%